Integration Of Dmaic Methodology And Capa Concept For Quality ImprovementIn Semiconductor Industry - Harun, Nurul Aida (2017)

(untitled)
The term quality in industry has been a key factor in measuring a firm competitiveness. Tools, methods, and concepts have been massively applied in improving and controlling product quality. Thus, industries urge themselves to cope with the needs of complete goods. In order to get a structured quality action, an organized framework is highly reliable. The purpose of this research is to develop a new problem solving framework where DMAIC (Define-Measure-Analyze-Improve-Control) is the main approach, with infusion of CAPA (Corrective and Preventive Action) concept. The DMAIC method is often described as an approach to problem-solving and a data-driven quality strategy as it is an integral part of the Six Sigma quality initiatives. Meanwhile, the CAPA concept is the systematic investigation of the root cause of identified risks or problems, widely implemented in industries. In this research, these two approaches are merged in designing a new quality reporting document named as the Quality Enhancement Action (QEA) report. The report presents the structured quality action in a more efficient way conducted in the electronics sector. The report has been validated through case studies and a survey through questionnaire. The outcomes confirmed the application and the practicality of the report as well as the new framework to improve quality issues. On the other hand, the quality report is not only focus on problem solving and decision making, but can break down organizational barriers. Through process and quality improvement, industries will have the capability in producing better goods in future.